Masters for Teacher Training: a locus of (re) construction and learning (Research, Society and Development, 2018)
The present study aims to analyze how the development of innovative pedagogical strategies linked to active teaching and learning methodologies are being carried out in the researches produced by postgraduate students at a Master's level of a University located in the interior of Rio Grande do Sul/Brazil. This is a qualitative study, with a descriptive exploratory approach. For the data collection, a bibliographic review of the academic production was carried out from 141 Master's dissertations from two Master's programs offered by the University. Data were collected through the University's Virtual Library. Of the total number of dissertations found, 43 presented clear indications of the use of active methodologies. These were analyzed and it was noticed that the active methodologies positively stimulated the students, as it instigated them to be more interested; in the classroom, in addition to developing their criticality and autonomy.